Virtual shadow puppet play with intelligent instructional tool and interactive real-time animation. (2015) - Piman, Sirot; Talib, Abdullah Zawawi; Osman, Mohd Azam
Shadow puppet play is one of the popular storytelling traditions in many parts of Asia. However, the tradition is becoming less and less popular nowadays due to the proliferation of new media entertainment. In this paper, we present the architecture of a software tool that allows people to experience shadow puppet play in the virtual world. Normally, a virtual puppet show is controlled automatically by the application. However, our tool allows the user to create storyline and control the puppets directly in real-time. This paper focuses in detail on the design and issues of two of the main components of an interactive virtual shadow puppet play which are the intelligent instructional tool for puppeteering and interactive virtual shadow puppet play animation. The result of the evaluation has shown that the tool is able to help users more beneficially and a higher degree of satisfaction among the respondents which include professional puppeteers and potential general users.